2021
DOI: 10.1002/da.23238
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity between the habenula and default mode network and its association with the antidepressant effect of ketamine

Abstract: Background: Recently, an animal model for depression has shown that ketamine, an N-methyl-D-aspartate receptor (NMDAR) antagonist, elicits a rapid-acting antidepressant effect by blocking NMDAR-dependent bursting in the lateral habenula (Hb). However, evidence from human studies remains scarce.Methods: This study explored the changes of resting-state functional connectivity (FC) of the Hb in responders and nonresponders who was diagnosed with unipolar or bipolar depression before and after ketamine treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 67 publications
(90 reference statements)
0
15
0
Order By: Relevance
“…There were no alterations observed in non-responders. The study results suggest that ketamine may suppress connectivity between habenula and DMN producing an antidepressant effect [ 74 ]. Considering the above-mentioned results, which suggest the progressive nature of FC changes in recurrent depression, it can be hypothesized that ketamine, by affecting the FC, can have a transformative role in TRD [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were no alterations observed in non-responders. The study results suggest that ketamine may suppress connectivity between habenula and DMN producing an antidepressant effect [ 74 ]. Considering the above-mentioned results, which suggest the progressive nature of FC changes in recurrent depression, it can be hypothesized that ketamine, by affecting the FC, can have a transformative role in TRD [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, additional treatment-related changes may remain undetected in a focused search, but we felt that this would be the most judicious approach to yield potentially important insights into treatment mechanisms. Third, due to the small size of the Hb and limited resolution fMRI, it is challenging to delineate its structure, distinguish between the lateral and medial Hb, and confirm whether the Hb signal is contaminated by the adjacent structure (Wang et al, 2022). Additionally, the relatively low signal-to-noise ratio in the midbrain ROIs might affect the stability of the results to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the FC between the whole-brain voxels and the DRN, VTA, and Hb, three spherical seed regions of interest (ROIs) with a radius of 3 mm were selected centered on three Montreal Neurological Institute (MNI) coordinates (shown in Supplemental Figure S2): the DRN (Faulkner et al, 2018) [MNI (x, y, z): 0, −28, −12], bilateral VTA (Murty et al, 2014) [MNI (x, y, z): left = −2.7, −15.9, −13.9; right = 4.1, −15.9, −13.9], and bilateral Hb (Lawson et al, 2013;Qiao et al, 2020;Wang et al, 2022) [MNI (x, y, z): left = −2.8, −24.2, 2.3; right = 4.8, −24.1, 2.2]. The seed point reference time series of each seed was calculated by averaging the time series within itself.…”
Section: Seed-based Fc Analysismentioning
confidence: 99%
“…As such, interconnectivity between major ICNs represents a promising candidate biomarker of rapid response to glutamate-mediating therapeutics that neuroimaging studies have actively explored. In particular, connectivity between the AN and DMN ( 161 ), RN and DMN ( 166 ), AN and RN ( 147 , 149 ), RN and CEN ( 147 ), DMN and CEN ( 138 ), DMN and SN ( 138 ), SN and SMN ( 158 ), CEN and SMN ( 145 , 212 ), AN and CEN ( 165 ), and AN and SN ( 165 ) have all been shown to be modulated by ketamine.…”
Section: Intrinsic Connectivity Network Biomarkers Of Ketamine Antide...mentioning
confidence: 99%
“…( 161 ) have shown that ketamine reduces bilateral sgACC connectivity with the DMN. Capitalizing on these findings, Wang et al further showed that ketamine responders displayed enhanced resting-state connectivity at baseline between the DMN hubs and lateral habenula (LHb), where ketamine-induced downregulation of aberrant LHb connectivity with parts of the DMN might have been attributed to a neural mechanism of ketamine antidepressant effects ( 166 ). Murrough et al ( 149 ) documented diminished activation of the right caudate nucleus during the presentation of negatively valenced emotional stimuli in TRD participants, which was normalized following ketamine administration.…”
Section: Intrinsic Connectivity Network Biomarkers Of Ketamine Antide...mentioning
confidence: 99%